1992
DOI: 10.1203/00006450-199210000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofen-Induced Diaphragmatic Hernias in Rats: Pulmonary Antioxidant Enzyme Activities

Abstract: ABSTRACT. We developed an experimental rat model of sive care and artificial ventilation (I). Mortality still remains at congenital diaphragmatic hernia (CDH) to elucidate the 50% as a result of pulmonary hypoplasia with or without peretiology and pathogenesis of this serious congenital anom-sistent pulmonary hypertension (2). Those infants with severe aly in humans and in particular to study the effects of a respiratory compromise need maximal ventilatory support and short period of artificial ventilation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 24 publications
3
8
0
1
Order By: Relevance
“…The results of fetal lung morphology and are in agreement with previous studies that observed fetuses of progressively smaller size when exposed to nitrofen (N-) and with CDH, pulmonary hypoplasia in both being higher in CDH than in C fetuses 14,29,30 . Ventilation for a short time did not significantly alter this pattern.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results of fetal lung morphology and are in agreement with previous studies that observed fetuses of progressively smaller size when exposed to nitrofen (N-) and with CDH, pulmonary hypoplasia in both being higher in CDH than in C fetuses 14,29,30 . Ventilation for a short time did not significantly alter this pattern.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 82%
“…The adaptation for ventilation in fetal rats was described in 1992 14 . However, this model was reproduced in only three other studies [15][16][17] .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We administered a single 100-mg dose of nitrofen at E9 and confirmed the diaphragm defects in 48% of the rat pups. This rate is acceptable as compared with those in other reports (19,20).…”
Section: Discussionsupporting
confidence: 49%
“…7,8,20,22 Possibly, the enhanced expression of HSPs in the CDH group reflects a neonatal attempt to establish a protective mechanism against stress, as shown earlier for antioxidant enzyme activity in a rat CDH model. 23 It has been well documented that the small-diameter pulmonary arteries are the most important vessels in the regulation of pulmonary blood flow and pressure. 2,3,19 Structural changes have been described in pulmonary arteries of patients with CDH complicated by PH.…”
Section: Discussionmentioning
confidence: 99%